A Systematic Literature Review of Project-Based Learning on Kindergarten Students Motor Development - Anisaturrahmi Anisaturrahmi; Sarah Fazilla; Mutia Sari; Muh Khairul Wajedi Imami (International Journal of Pedagogy and Learning Community (IJPLC), 2026)
The current research is a systematic literature review examining the impact of project-based learning (PBL) on kindergarten students’ motoric development. The review focuses on the types of projects implemented, targeted motoric aspects, and methodological characteristics of previous studies. An initial search was conducted across three databases—Scopus, ERIC, and Google Scholar—and the selected studies were screened using the PRISMA protocol to ensure validity and relevance. Following the selection process, 30 publications were included for analysis. The findings show that research on this topic first emerged in 2015, with the highest number of publications occurring in 2024 (11 studies), involving a total of 548 kindergarten students. Collage-making was the most frequently implemented project, followed by sewing and origami activities. Most studies emphasized fine motor development, particularly hand–eye coordination, cutting, folding, pasting, grasping, writing, and drawing skills. Quantitative quasi-experimental designs were predominantly employed. Overall, the findings indicate a significant positive impact of PBL on kindergarten students’ motoric development, contributing valuable insights for early childhood education practice and research.